155k views
4 votes
4y - 7 = 5x2 - x + 2 + 3y

Quadratic Equations
Options are No, One, Two.
I don't remember learning how to do it with more than a, b, and c variable. I'm so confused please help.

User Yuhi
by
4.6k points

1 Answer

1 vote

Answer:

y = 9 + -1x + 5x2

Explanation:

Simplifying

4y + -7 = 5x2 + -1x + 2 + 3y

Reorder the terms:

-7 + 4y = 5x2 + -1x + 2 + 3y

Reorder the terms:

-7 + 4y = 2 + -1x + 5x2 + 3y

Solving

-7 + 4y = 2 + -1x + 5x2 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.

-7 + 4y + -3y = 2 + -1x + 5x2 + 3y + -3y

Combine like terms: 4y + -3y = 1y

-7 + 1y = 2 + -1x + 5x2 + 3y + -3y

Combine like terms: 3y + -3y = 0

-7 + 1y = 2 + -1x + 5x2 + 0

-7 + 1y = 2 + -1x + 5x2

Add '7' to each side of the equation.

-7 + 7 + 1y = 2 + -1x + 7 + 5x2

Combine like terms: -7 + 7 = 0

0 + 1y = 2 + -1x + 7 + 5x2

1y = 2 + -1x + 7 + 5x2

Reorder the terms:

1y = 2 + 7 + -1x + 5x2

Combine like terms: 2 + 7 = 9

1y = 9 + -1x + 5x2

Divide each side by '1'.

y = 9 + -1x + 5x2

Simplifying

y = 9 + -1x + 5x2

User Mats Raemen
by
5.2k points